Balancing the COVID-19 Disruption to Undergraduate Learning and Assessment with an Academic Student Support Package : Implications for Student Achievement and Engagement. - Lloyd, Natalie; Sealey, Rebecca; Logan, Murray (Student Success v.12 n.2 p.61-71 https://doi.org/10.5204/ssj.1933, 2021)
In response to the COVID-19 pandemic-induced emergency pivot to online teaching and assessment, an Academic Safety Net was implemented at a regional Australian university to provide academic student support. Bayesian hierarchical models were used to compare student performance between 2019 and 2020. More students withdrew from subjects in 2020, while fewer students remained enrolled but failed. While there was no overall year effect for overall student achievement, exam achievement increased and on-course assessment achievement decreased in 2020. When achievement was analysed according to an assessment task change, a year effect emerged, with the magnitude and direction of the effect dependent on the task changes. The results indicate that the enrolment component of the Academic Safety Net was an effective equity measure that enabled students an extended opportunity to self-withdraw in response to general impacts of the pandemic; while the results component protected the integrity of results awarded during the emergency pivot. [Author abstract]